Stress, health & well-being thriving in the 21st century - Harrington, Rick (Belmont, CA Wadsworth Cengage Learning, 2013)
Explores how stress affects health, the benefits and negative aspects of stress, and ways to manage stress to live a healthy life.
Stress, health, and positive psychology -- The biology of stress and illness -- Stress, personality, and emotions -- Interpersonal and job stress -- Emotional and behavioral self-regulation -- Mind-body strategies -- Guidelines for stress management and well-being enhancement.
Includes bibliographical references (p. 489-521) and indexes.
Keywords: Stress (Psychology) -- 21st century; Stress (Physiology) -- 21st century; Stress management -- 21st century